Popular Religion, Sacred Natural Sites, and Marian Verdant Advocations in Spain - Tatay-Nieto, Jaime; Muñoz-Igualada, Jaime (2019)
A relevant number of shrines, hermitages, monasteries, and pilgrimage routes in Spain are located within or near Natura 2000, a European network of protected core breeding and resting sites for rare and threatened species, and some rare natural habitat types. Given the growing interest in alternative conservation strategies and the geographical correlation between nature preserves and Sacred Natural Sites (SNS), this paper explores how religious devotions have made preservation possible in Spain. By an extensive literature review and interviews with long-established custodians of nonurban Marian sanctuaries, it looks at the development of plant-related allegorical titles, the multiple meanings of Marian verdant advocations, and the role popular religion has played in connecting theological insights with particular elements of natural ecosystems helping value and preserve the Spanish biocultural heritage. We found that 420 Marian titles directly refer to plant species or vegetation types and many of the nonurban Marian sacred sites are placed in well-preserved natural areas, some of them playing a human-related added value for most emblematic National Parks, like the sanctuaries of El Rocío (Doñana NP) and Covadonga (Picos de Europa NP). We conclude that there is a strong relationship between popular religion, Marian verdant titles, and nature conservation.
Keywords: Christianity; Mariology; Natura 2000; Plants; biocultural diversity; popular religion; religion and nature